Defying the “Illiberal” Gig Economy: Coping Strategies of Freelance Domestic Workers in the United Arab Emirates - Froilan Malit (Global Labour Journal)
How do low-skilled migrant workers navigate restrictive gig economies in illiberal host states of the Global South? Despite the growing gig economy, scholars have yet to examine the linkage between the politics of the gig economy and migrant resilience in illiberal host states in the Global South. Using a single case study of freelance Filipina domestic workers in the UAE (N = 20), I argue that, despite facing legal and economic risks (penalties), freelance migrant workers have produced an informal freelancing visa system to contest the formal and hierarchical segmentation of the gig economy via three diverse strategies: co-optation, tapping and brokering. These evasive social coping strategies mirror their collective resistance against structural labour exploitation and reinforce their autonomous role in the social (re)production of community solidarity within informal gig economies. Overall, this study contributes to empirical and theoretical discourse on the politics of illiberal migration management and the gig economy by featuring female migrant freelancers’ complex social agency within illiberal gig economies in the Global South.